Coasts, Marine Structures and Breakwaters 2017 : Realising the potential - Burgess, Kevin (ICE Publishing, 2018)
The ICE Coasts, Maritime Structures and Breakwaters conference series, sponsored by the ICE for over 30 years, is the leading international forum for the presentation of the latest developments in coastal and maritime engineering. The 11th conference, Realising the Potential, was held in Liverpool from 5th to 7th September 2017. It was attended by over 300 delegates and saw 90 papers presented. This book contains the full discussion notes from each session at the conference as well as 'innovation spotlights' detailing short presentations on new and developing practices and processes. The topics for 2017 focused on describing the design, construction, analysis and performance of a wide range of maritime structures. The contents contain the latest research and developments and up-to-date guidance and innovations as well as practical lessons learned from experience.
Keywords: Coastal engineering -- Congresses.; Shore protection -- Congresses.; Breakwaters -- Design and construction -- Congresses.; elektronické knihy; electronic books